Relación entre la angustia psicológica y el mobbing en las organizaciones - Vicente Palomino, Mauricio (2021)
Workplace bullying is a serious public health problem due to its negative effects such as psychological distress: A state of suffering, stress, and disability. The objective of this study is to examine the association between mobbing and psychological distress through applied review report of previous literature in this area. A systematic review was conducted considering the following indications of the PRISMA guidelines (Urrútia & Bonifill, 2013). The databases consulted according to the inclusion criteria of studies that evaluated the relationship between workplace bullying and psychological distress: Proquest, Scopus and Pubmed. On the other hand, qualitative, normative, thesis, books and proceedings that were not published in scientific journals were used as methods of exclusion studies. The total of research based on the inclusion and exclusion criterion (n = 8) were selected for analysis. In each of the selected articles the relationship between the variables of mobbing and psychological distress is evidenced, either as a predictor or consequence of the other. Limitations were found due to the lack of explicit theoretical models and psychometric properties. However, the analysis of the articles confirms that there is a relationship between mobbing and psychological distress.